2024
DOI: 10.1038/s41467-024-49142-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot laser-driven neutron resonance spectroscopy for temperature profiling

Zechen Lan,
Yasunobu Arikawa,
Seyed Reza Mirfayzi
et al.

Abstract: The temperature measurement of material inside of an object is one of the key technologies for control of dynamical processes. For this purpose, various techniques such as laser-based thermography and phase-contrast imaging thermography have been studied. However, it is, in principle, impossible to measure the temperature of an element inside of an object using these techniques. One of the possible solutions is measurements of Doppler brooding effect in neutron resonance absorption (NRA). Here we present a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A PMT with gated voltage can reduce the impact of the flash signals [27][28][29] . Neutron resonance transmission experiments using LDNSs have been reported [30][31][32] . Drops in neutron counts at the neutron resonance energies in a spectrum were observed from 18 laser shots using a borated microchannel plate (MCP) detector, which has low sensitivity to gamma rays 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PMT with gated voltage can reduce the impact of the flash signals [27][28][29] . Neutron resonance transmission experiments using LDNSs have been reported [30][31][32] . Drops in neutron counts at the neutron resonance energies in a spectrum were observed from 18 laser shots using a borated microchannel plate (MCP) detector, which has low sensitivity to gamma rays 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Drops in neutron counts at the neutron resonance energies in a spectrum were observed from 18 laser shots using a borated microchannel plate (MCP) detector, which has low sensitivity to gamma rays 30 . The changes in neutron transmission at the neutron resonance energies were observed by monitoring the output level of a time-gated 6 Li glass scintillation neutron detector with a single laser shot 31,32 . This study observed the neutron resonance transmission spectrum using a counting method with a time-gated 6 Li glass scintillation neutron detector.…”
Section: Introductionmentioning
confidence: 99%